Use of anti-CD20 therapy in follicular and marginal zone lymphoma: a review of the literature - Juárez-Salcedo, Luis Miguel (Drugs Context, 2020)
The identification of the CD20 antigen in 1979 was the first step in what would become a therapeutic milestone opening the use of immunotherapy in hematological diseases. This protein is expressed on the surface of developing B cells, but not the early progenitors or mature plasma cells. In 1997, rituximab was approved by the Food and Drug Administration, and since then it has revolutionized the treatment of B-cell malignancies. It is used as a monotherapy and in combination, at induction, at relapsed, and also in maintenance. Indolent non-Hodgkin lymphomas are characterized by a long and non-aggressive course. In this group of lymphomas, rituximab represented a great therapeutic improvement, achieving lasting responses with few adverse effects. Nowadays, second-generation molecules are emerging that may have important advantages compared to rituximab, as well as biosimilars that represent an important cost-effective option.